15 Does The Patellar Tendon Respond To 5 Days Of Loading During A Volleyball Tournament?. (5th September 2014) - van Ark, Mathijs; Docking, Sean; van den Akker-Scheek, Inge; Rudavsky, Aliza; Rio, Ebonie; Zwerver, Johannes; Cook, Jill
Abstract : Introduction: Patellar tendinopathy (jumper's knee – pain in the tendon and dysfunction) has a high prevalence, especially in jumping athletes like volleyball players. Excess load on the patellar tendon through high volumes of training and competition is an important risk factor [Visnes, 2014]. Structural changes in the tendon are related with a higher risk of developing patellar tendinopathy [Cook, 2000]. The critical load that affects tendon structure is unknown. The aim of this study was to investigate patellar tendon structure on each day of a five day volleyball tournament in an adolescent population (16–18 years old). Methods: The right patellar tendon of 41 players in the Australian Volleyball Schools Cup (AVSC) was scanned with Ultrasound Tissue Characterisation (UTC) on every day of the tournament (Monday-Friday). UTC can quantify structure of a tendon into four echo-types based on the stability of the echopattern. Hypoechoic abnormalities on grey-scale were also recorded at baseline. Generalised Estimating Equations (GEE) were used to test for change of echo-type I and II over the tournament. Echo-type was used as dependent variable; main effect of time (days of tournament) was determined. In a second analysis the interaction effect time by hypoechoic abnormality was determined. Results: Participants played between 8 and 9 matches during the tournament. Hypoechoic abnormalities were recorded in 14 athletes. There was no significant change in echo-types over the 5 days of the study (echo-type I: Wald χ 2 =4.603, df = 4, p = 0.331; echo-type II: Wald χ 2 = 6.070, df=4, p = 0.194; see figure 1 ). Overall echopattern was stable across the tournament in participants without hypoechoic abnormalities while a (non-significant) decrease in echo-type I (less stable echopattern) over time (Wald χ 2 = 3.853, df =4, p = 0.426) was seen in athletes with hypoechoic abnormalities (figure 2 ). Echo-type I was significantly lower in athletes with abnormalities (Wald χ 2 = 16.545, df=1, p < 0.001). Discussion: This study shows that patellar tendon structure of 16–18 year old volleyball players is not affected during 5 days of cumulative loading during a volleyball tournament. Subgroups might exist with a different response to load (e.g. existing hypoechoic abnormality). Further research should focus on different loads and subgroups. References: Visnes et al . Scan J Med Sci Sports. 2014;[Epub] Cook et al . J Ultrasound Med . 2000;19:473–479